2022
DOI: 10.1051/0004-6361/202244542
|View full text |Cite
|
Sign up to set email alerts
|

3D non-LTE iron abundances in FG-type dwarfs

Abstract: Iron is one of the most important elements in-stellar astrophysics. However, spectroscopic measurements of its abundance are prone to systematic modelling errors. We present three dimensional non-local thermodynamic equilibrium (3D non-LTE) calculations across 32 STAGGER-grid models with effective temperatures from 5000 K to 6500 K, surface gravities of 4.0 dex and 4.5 dex, and metallicities from −3 dex to 0 dex, and we study the effects on 171 Fe i and 12 Fe ii optical lines. In warm metal-poor stars, the 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…This can be explained by the stellar parameter differences adopted in both studies, as well as the difference between line lists. However, as noted in Amarsi et al (2016), Amarsi et al (2022), 3D corrections can nevertheless be smaller than the NLTE corrections determined for low metallicity evolved stars. Therefore, including 1D, NLTE corrections in the determination of Fe I and Fe II lines can significantly improve the derived stellar parameters as compared to 1D, LTE.…”
Section: Caveatsmentioning
confidence: 68%
“…This can be explained by the stellar parameter differences adopted in both studies, as well as the difference between line lists. However, as noted in Amarsi et al (2016), Amarsi et al (2022), 3D corrections can nevertheless be smaller than the NLTE corrections determined for low metallicity evolved stars. Therefore, including 1D, NLTE corrections in the determination of Fe I and Fe II lines can significantly improve the derived stellar parameters as compared to 1D, LTE.…”
Section: Caveatsmentioning
confidence: 68%
“…The full 3D non-LTE analysis increased the upper limit on the Fe abundance for this star to [Fe/H] < −6.53 as compared to the previous non-LTE upper limit of [Fe/H] < −7.52 computed using averaged 3D (⟨3D⟩) model atmospheres (Bessell et al 2015). Additionally, recent work on C and O (Amarsi et al 2016a), Li (Wang et al 2021), and Fe (Amarsi et al 2016b(Amarsi et al , 2022 have also demonstrated significant 1D LTE-3D non-LTE abundance corrections for metal-poor stars.…”
Section: Introductionmentioning
confidence: 67%
“…These analyses are strongly sensitive to the approximations employed when modelling the synthetic spectra. The abundance offsets introduced by the simplifying assumptions of one-dimensional (1D) hydrostatic atmospheres and local thermodynamic equilibrium (LTE) have been shown to be particularly severe at lower metallicities (Amarsi et al 2016b(Amarsi et al , 2022Bergemann et al 2012Bergemann et al , 2019Ezzeddine et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The right panel in Figure 9 shows this in detail, alongside the observed spectrum of HD122563, a star with similar parameters, from GALAH (Buder et al 2021). Given that accurate modeling of H α core requires techniques beyond 1D LTE (e.g., Barklem 2007;Amarsi et al 2018), and that the observational data does not match the prediction of any of the codes, we consider this disagreement permissible.…”
Section: Balmer Seriesmentioning
confidence: 99%
“…Eliminating the former two assumptions means calculating atmospheric structure using the full hydrodynamic equations (e.g., Freytag et al 2012;Magic et al 2015;Schultz et al 2022) or the magnetohydrodynamic equations (e.g., Vögler et al 2005), if the internal magnetic field is strong. Fortunately, corrections to 1D LTE level populations (e.g., Amarsi et al 2020Amarsi et al , 2022, equivalent widths, or abundances (e.g., Lind et al 2011;Bergemann et al 2012;Amarsi et al 2015;Osorio & Barklem 2016) can be calculated from non-LTE (NLTE) simulations. These can be applied to LTE results or codes to produce approximate NLTE spectra at relatively little computational cost.…”
Section: Introductionmentioning
confidence: 99%